Morphometric study of vertebral artery groove in dry human cervical vertebra in Pakistani population - Mohtasham Hina, Maria Tasleem, Ammara Rasheed, Raafea Tafweez (Journal of Rawalpindi Medical College, 2021)
Introduction: Vertebral artery passes through vertebral artery groove present on the posterior arch of atlas; free movement of which is required during rotation of the neck. This artery can be compressed if the vertebral groove is converted into arcuate foramina due to the projection of bony ponticuli over the grove. This compression can cause vertebra-basilar insufficiency, headache, or neck-shoulder pain of unknown origin. Objective: This study aims to provide data regarding vertebral artery groove and its morphology to help surgeons and clinicians in the local Pakistani population as no data is available in this population. Materials and Methods: A total of sixty adult dry human atlas vertebrae were taken from the Anatomy museum of King Edward medical university. Quantitative and qualitative data were taken for analysis. Quantitative data include the distance of medial and lateral edges of vertebral artery groove from the midline of the posterior arch, the distance of the medial edge of foramen transversarium from the midline, the thickness of vertebral artery groove and its dimensions at medial and lateral entrance points. Qualitative data includes the type of bridging over the vertebral artery groove. Data were analyzed and the mean was taken. Results: Mean distance of the medial edge of vertebral artery groove from midline was found to be 13.32 ± 3.25 and 13.72 ± 2.82 mm on right and left sides respectively while the mean distance of the lateral edge of vertebral artery groove from midline was 22.31 ± 3.47 on the right side and 22.29 ± 2.98 on the left side. The mean of total thickness found was 3.84 ± 0.66 mm on right and 3.57 ± 1.14 mm on left. Morphology showed that 3.33% of the Pakistani population has complete arcuate foramina, 40% partial bridging, and 56.67% absent bridging. Conclusion: Findings of this study can be helpful for neurosurgeons during procedures requiring exposure of the posterior arch of the atlas so that damage to a vertebral artery can be prevented.